Literature Review: Cyberbullying in Addolescence - Marpatmawati, Idhfi; Yuningsih, Aneng; Rismawan, Wawan; Milda Hidayat, Nandita (KIAN JOURNAL, 2024)
Introduction: Cyberbullying is a growing phenomenon with the increasing use of digital technology and social media among adolescents. This phenomenon can affect adolescents' mental and emotional well-being, even having long-term impacts on their psychological health. This study aims to reveal the prevalence, risk factors, and psychological impact of cyberbullying among adolescents. Objective: This study aims to explore the prevalence, risk factors, and psychological impact of cyberbullying among adolescents, with a focus on the relationship between cyberbullying and mental health outcomes such as depression, anxiety, and suicidal ideation. Method: This study used a literature search design with articles searched through three search engines: Ebsco, Proquest, and Google Scholar. The articles used were research conducted within the last five years (2020-2025), using the keywords "cyberbullying," "adolescence," and "effects." A total of 594 articles were found, which were then narrowed down to nine articles that met the inclusion criteria. Result: This study found that the prevalence of cyberbullying among adolescents globally ranges from 13.99% to 57.5%. Key risk factors include personal characteristics such as age, gender, and online behavior. The most common psychological impacts include decreased happiness, increased anxiety, depression, and an increased risk of suicide, especially for those who experience cyberbullying alongside traditional bullying. Conclusion: Cyberbullying has a significant impact on adolescent mental health, particularly in the form of psychological disorders such as depression and anxiety. Therefore, preventive efforts involving parents, schools, and the community are crucial to mitigate the negative impact of this phenomenon. Emotional education and strong parent-child relationships can help prevent cyberbullying.